8 Weeks of High-Intensity Interval Training (HITT) to Increase Vo2max, Muscular Endurance Student Activity Units Basketball Universitas PGRI Jombang - Setyawan, Risfandi (International Journal of Basketball Studies, 2023)
The background of this research is the less Endurance which belongs to the basketball players. The purpose of this research is to know the effect of training High-Intensity Interval Training (HIIT) to the improvement of Vo2max and endurance muscle to know how effective the training High-Intensity Interval Training (HIIT) to the improvement of VO2max and muncle endurance. This research is a kind of experiment research by using the design total population The population of this research is the men basketball player of STKIP PGRI Jombang which consist of 20 students. average age 19 years Height ± 166.31cm, weight ± 58.63kg. , 8 weeks for treatment (treatment). Post test measurements were taken 48-72 hours after the last treatment, measurement test :Vo2max MFT Multistage Fitness Test, Leg muscle endurance using Bench Jump. The result of this research can be known that the training design Interval Training gives the significant result to the improvement of Vo2max. Based on the result of analysis, (1) there is effect of High_intensity Interval Training (HIIT) to the improvement of VO2max (sig. = 0.000 < α = 0.05). (2) High Intensity Interval Training (HIIT) to the improvement of knee muscle endurance, (sig. = 0.000 < α = 0.05).